Dissociations between emotional and linguistic prosody in patients with right hemisphere lesions - Leiva, Samanta (2017)
The goal of this study was to evaluate dissociation patterns between processing of linguistic prosody and emotional (or affective) prosody, in order to analyze the functional independence between them. We carried out a multiple single-cases study of 17 patients with right hemisphere lesions due to stroke. The alteration / conservation profiles of the ability to process both types of prosody were analyzed with four tasks of comprehension and repetition of emotional and linguistic prosody. The performance of each patient was compared with a healthy control group. The results showed a dissociated performance between emotional and linguistic prosody in prosodic comprehension in 3/17 patients, and no double dissociations were found. Finding different patterns of alteration / conservation between linguistic and emotional prosody, both in the ability to understand and to repeat prosody, supports the assumption of functional independence between processing of both types of prosody. Doi: https://doi.org/10.24265/liberabit.2017.v23n2.04